HUBUNGAN PENGETAHUAN WUS TENTANG KANKER PAYUDARA DENGAN PERILAKU SADARI - Auliana, Nisfi Laeli; Utami, Tin; Haniyah, Siti (Coping: Community of Publishing in Nursing; Vol 11 No 2 (2023): April 2023DO - 10.24843/coping.2023.v11.i02.p09, 2023)
Breast cancer is a malignancy found in breast tissue in cells originating from its glandular components, namely the epithelium and its lobules and components other than glands, namely the innervation of breast tissue, blood vessels and fat tissue. According to the World Health Organization (WHO) in 2020 globally there are 2,3 million women diagnosed with breast cancer and 685.000 deaths. One of the efforts to prevent and control breast cancer is to do breast self-examination behavior (BSE). This study aims to determine the relationship between WUS knowledge about breast cancer and BSE in Desa Karangpucung. This research method is correlational descriptive with cross sectional approach with sampling purposive sampling technique. The number of samples in this research were 97 respondents. Data analysis using Spearman rank test. Collecting data using a breast cancer knowledge questionnaire and BSE behavior. The results showed that there was correlation of knowledge of childbearing age women on breast cancer and BSE with a p-value = 0,000 (p<0,05) with correlation coefficient value = 0,574.